Micro-drilling of Ti-6Al-4V alloy: The effects of cooling/lubricating - KAYNAK, YUSUF (ELSEVIER SCIENCE INC, 2016)
This paper presents a series of experimental investigations of the effects of various machining conditions [dry, flooded, minimum quantity lubrication (MQL), and cryogenic] and cutting parameters (cutting speed and feed rate) on thrust force, torque, tool wear, burr formation, and surface roughness in micro-drilling of Ti-6Al-4V alloy. A set of uncoated carbide twist drills with a diameter of 700 mu m were used for making holes in the workpiece material. Both machining conditions and cutting parameters were found to influence the thrust force and torque. The thrust force and torque are higher in cryogenic cooling. It was found that the MQL condition produced the highest engagement torque amplitude in comparison to the other coolant-lubrication conditions. The maximum average torque value was obtained in the dry drilling process. There was no substantial effect of various coolant-lubrication conditions on burr height. However, it was observed that the burr height was at a minimum level in cryogenic drilling. Increasing feed rate and decreasing spindle speed increased the entry and exit burr height. The minimum surface roughness values were obtained in the flood cooling condition. In the dry drilling process, increased cutting speed resulted in reduced hardness on the subsurface of the drilled hole. This indicates that the surface and subsurface of the drilled hole were subject to softening in the dry micro-drilling process. The softening at the subsurface of drilled holes under different cooling and lubrication conditions is much smaller compared to the dry micro-drilling process. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Micro-drilling; Ti-6Al-4V; Minimum quantity lubrication; Cryogenic cooling; Surface integrity; Surface roughness; SURFACE INTEGRITY; THRUST FORCE; TITANIUM-ALLOYS; TOOL WEAR; DRY; ROUGHNESS; COMPOSITE; BURR; MQL